Komunitas Airbrush Indonesia Dalam Rana Seni Rupa - Lestari, Dina (Institut Seni Indoensia Surakarta, 2012)
Indonesia Airbrush community was founded in 2007 by MG. Pringgotono, an airbrush artist from Jakarta. Members that are joining this community came from different places in Indonesia such as Jakarta, Yogyakarta, Bandung, Lampung, Palembang, Solo, Tanggerang, Tuban, Serang, Bekasi, Pematang Siantar, Ngawi, Bali, Kediri, Bangka Belitung and many more. This community was build as a reaction to respond the influence of commercial industry on airbrush developmental image branding by making a change and expanding to the realm of visual art. Their vision and mission is to support the Indonesian airbrush artists, mapping, and collecting data and archive of Indonesian airbrush development by providing information and developing Indonesian airbrusher as a preparation for the creative era. Some of their program is to hold a workshop, an airbrush art exhibition, compiling Indonesian airbrush art work catalogues, held an Indonesian airbrush artist meeting gathering, arranging an airbrush competition and operatingÂ an airbrush website which is Airbrush Indonesia websites.Â Keyword: Airbrush, Indonesia, Community and Visual Art